2007
DOI: 10.1039/b703344c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast IR spectroscopy of the short-lived transients formed by UV excitation of cytosine derivatives

Abstract: A strong infrared band at 1574 cm 21 is observed following 267 nm excitation of 29-deoxycytidine (t = 37 ¡ 4 ps) or 29-deoxycytidine 59-monophosphate (t = 33 ¡ 4 ps); this band is provisionally attributed to an 1 n N p* state and is absent for cytosine.The nature of the electronic excited states of DNA continues to be a focus of significant interest because of their role in UV-light induced modifications that could potentially be mutagenic. 1 The nucleobases fluoresce extremely weakly and this has led to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(108 citation statements)
references
References 30 publications
12
96
0
Order By: Relevance
“…1, 3 However, it is known that very simple modifications of nucleic acids, such as chemical substitution or the presence of a ribose group or protonation, may significantly change the excited state lifetimes. 17 In this light the protonation of 5¢-GMP to form 5¢-GMPH + (2) (pK a = 2.3) is known to have a dramatic effect on the lifetime of the electronic excited state. The protonated form is significantly more fluorescent than the neutral base.…”
Section: Introductionmentioning
confidence: 99%
“…1, 3 However, it is known that very simple modifications of nucleic acids, such as chemical substitution or the presence of a ribose group or protonation, may significantly change the excited state lifetimes. 17 In this light the protonation of 5¢-GMP to form 5¢-GMPH + (2) (pK a = 2.3) is known to have a dramatic effect on the lifetime of the electronic excited state. The protonated form is significantly more fluorescent than the neutral base.…”
Section: Introductionmentioning
confidence: 99%
“…This is in good agreement with that measured for the parent nucleobase cytosine, which undergoes rapid single exponential decay with a lifetime of 4.4  0.4 ps. 5 The similarity in kinetics between cytosine and 1-mCyt leads us to assign the observed TRIR activity to rapid crossing from the electronic excited potential energy surface (PES) to the ground-state PES (via internal conversion from the 1 ππ* state) creating vibrationally hot ground state molecules, formed with up to 34,000 cm -1 excess energy. Turning our attention to 5'-dCMP, we see that the TRIR spectra ( Figure 2a) are clearly different from that of 1-mCyt.…”
Section: Figure 1 Family Of Cytosine Derivatives With Different N1 Smentioning
confidence: 99%
“…;Evidence of the non-emissive decay route for electronically excited cytosine derivatives has been obtained from both transient UV/vis 4 and time-resolved infrared (dCyd and 5'-dCMP) spectroscopies. 5 The relatively long-lived (34-37 ps) species has been assigned as a 1 nπ* state and is formed in moderate yields. 4 In our TRIR study a strong transient absorption band centred at 1574 cm -1 was observed.…”
Section: A Comparative Picosecond Transient Infra-red Study Of 1-methmentioning
confidence: 99%
“…4 To fully understand the nature of the molecular specific interactions, it is essential to employ techniques that can interrogate the structural modifications underpinning these processes, and here we apply ultrafast time-resolved infrared spectroscopy (TRIR) for this purpose. ps-TRIR is now being demonstrated as a powerful technique for probing the photophysical properties of DNA, [5][6][7][8] and its strength stems from its ability to yield kinetic and structural information that goes beyond that obtainable from fluorescence or transient UV/visible absorption techniques.In this communication, we describe how ps-TRIR can be employed to investigate conformationally dependent photophysical properties of base-base interactions. Guanine is known to aggregate to form stacked species at high concentrations.…”
mentioning
confidence: 99%